Spatiotemporal dependence of Antarctic sea ice variability to dynamic and thermodynamic forcing: a coupled ocean–sea ice model study - Kusahara, K; Guy Williams; Robert Massom; Phillip Reid; Hasumi, H (2019)
Satellite-derived Antarctic sea ice extent has displayed a slight upward since 1979, but with strong temporal and regional variability—the drivers of which are poorly understood. Here, we conduct numerical experiments with a circum-Antarctic ocean–sea ice–ice shelf model driven by realistic atmospheric surface boundary conditions to examine the factors responsible for the temporal and spatial patterns in observed Antarctic sea ice variability. The model successfully reproduces observed seasonal and interannual variability in total sea ice extent and the temporal/spatial patterns of sea ice concentration and seasonality (days of advance and retreat and actual ice days) for 1979–2014. Sensitivity experiments are performed, in which the interannual variability in wind stress or thermodynamic surface forcing is ignored, to delineate their contributions to Antarctic sea ice fields. The results demonstrate that: (1) thermodynamic forcing plays a key role in driving interannual variability in sea ice extent and seasonality in most Antarctic sectors; (2) only in the Ross Sea the wind stress does become the main driver of sea ice extent variability; (3) thermodynamic forcing largely regulates interannual variability in the timing of sea ice advance, while wind stress largely controls the timing of the sea ice retreat; and (4) although both wind stress and thermodynamic forcing contribute to variability in total sea ice volume, the wind stress plays a dominant role in regulating sea ice volume variability in the near-coastal zone.